2010
DOI: 10.1128/iai.00002-10
|View full text |Cite
|
Sign up to set email alerts
|

CD1d-Dependent B-Cell Help by NK-Like T Cells Leads to Enhanced and Sustained Production of Bacillus anthracis Lethal Toxin-Neutralizing Antibodies

Abstract: The current Bacillus anthracis vaccine consists largely of protective antigen (PA), the protein of anthrax toxin that mediates entry of edema factor (EF) or lethal factor (LF) into cells. PA induces protective antibody (Ab)-mediated immunity against Bacillus anthracis but has limited efficacy and duration. We previously demonstrated that activation of CD1d-restricted natural killer-like T cells (NKT) with a CD1d-binding glycolipid led to enhanced Ab titers specific for foreign antigen (Ag). We therefore tested… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
27
2
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 33 publications
3
27
2
1
Order By: Relevance
“…Several recent reports provide evidence that ␣GalCer and its analog could be an effective adjuvant in the immunization protocol (8,18,20). With the understanding of the interaction of RA and ␣GalCer, the combination may be promising for improving vaccine effectiveness in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Several recent reports provide evidence that ␣GalCer and its analog could be an effective adjuvant in the immunization protocol (8,18,20). With the understanding of the interaction of RA and ␣GalCer, the combination may be promising for improving vaccine effectiveness in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Preclinical results highlight the efficacy and attractiveness of the use of vaccine containing αGalCer simply mixed with protein Ags derived from a variety of infectious pathogens, to activate noncognate B-cell help by iNKT cells and induce efficient protective humoral responses and long-lasting memory through mucosal and parenteral administration routes [43,[46][47][48][49].…”
Section: Noncognate Help By Inkt Cellsmentioning
confidence: 99%
“…Also, intratracheal inoculation with the NKT superagonist alpha-galactosylceramide (␣GC) stimulates NKT cell activation in pig lungs (Renukaradhya et al, 2011). Previous reports have demonstrated that NKT cell superagonisits can protect mice from several pathogens that affect swine, including influenza (Ho et al, 2008), Pseudomonas aeruginosa (Minagawa et al, 2005;Nieuwenhuis et al, 2002), Streptococcus pneumoniae (Nakamatsu et al, 2007), Mycobacterium tuberculosis (Chackerian et al, 2002;Sada-Ovalle et al, 2010), Listeria monocytogenes (Emoto et al, 2010), Staphylococcus aureus (Lin et al, 2010), cytomegalovirus (van Dommelen et al, 2003), Trypanosoma cruzi (Duthie and Kahn, 2002), Japanese encephalitis virus (Lin et al, 2010) and Bacillus anthrax (Devera et al, 2010). In addition, the adjuvant effects of NKT cell superagonists have been exploited in mice to improve vaccines against microorganisms that also infect pigs, including influenza (Guillonneau et al, 2009;Ko et al, 2005;Kopecky-Bromberg et al, 2009;Lee et al, 2011;Youn et al, 2007), M. tuberculosis (Venkataswamy et al, 2009) and B. anthrax (Devera et al, 2010).…”
Section: Introductionmentioning
confidence: 99%